2022
DOI: 10.1002/admi.202200915
|View full text |Cite
|
Sign up to set email alerts
|

Esaki Diode Behavior in Highly Uniform MoS2/Silicon Carbide Heterojunctions

Abstract: The heterogeneous integration with 2D materials enables new functionalities and novel devices in state‐of‐the‐art bulk (3D) semiconductors. In this work, highly uniform MoS2 heterostructures with silicon carbide (4H‐SiC) are obtained by a facile synthesis method, highly compatible with semiconductor fab processing, i.e., the sulfurization of predeposited very‐thin (≈1.2 nm) Mo films at a temperature of 700 °C. Current–voltage characteristics of MoS2/n+‐4H‐SiC junctions collected by conductive atomic force micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 51 publications
(70 reference statements)
1
17
0
Order By: Relevance
“…This has been achieved by oxygen plasma post-treatments of exfoliated or CVDgrown MoS 2 , [45,46] associated with unintentionally incorporated oxygen during MoS 2 deposition [47] or the presence of MoO 3 residuals in MoS 2 layers produced by sulfurization of predeposited MoO x films. [18,25,48] In particular, we recently demonstrated the formation of a highly p-type-doped 1L MoS 2 on 4H-SiC by the sulfurization approach, in the presence of MoO 3 detected by XPS analyses [18] Interestingly, no MoO 3 contributions were detected by XPS analyses on the CVD-grown MoS 2 sample. Hence, we expect that the p-type doping of MoS 2 on 4H-SiC deduced by Raman measurements can be related to charge transfer phenomena at the interface between these materials.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This has been achieved by oxygen plasma post-treatments of exfoliated or CVDgrown MoS 2 , [45,46] associated with unintentionally incorporated oxygen during MoS 2 deposition [47] or the presence of MoO 3 residuals in MoS 2 layers produced by sulfurization of predeposited MoO x films. [18,25,48] In particular, we recently demonstrated the formation of a highly p-type-doped 1L MoS 2 on 4H-SiC by the sulfurization approach, in the presence of MoO 3 detected by XPS analyses [18] Interestingly, no MoO 3 contributions were detected by XPS analyses on the CVD-grown MoS 2 sample. Hence, we expect that the p-type doping of MoS 2 on 4H-SiC deduced by Raman measurements can be related to charge transfer phenomena at the interface between these materials.…”
Section: Resultsmentioning
confidence: 96%
“…demonstrating advanced photodetectors operating both in the visible and in the ultraviolet (UV) spectral range [10][11][12][13] and innovative heterojunction diodes for fast switching and low-power consumption electronics. [14][15][16][17][18] The hexagonal structure of 4H-SiC and GaN and the very low lattice mismatch with MoS 2 on the basal plane (%2.9% in the case of 4H-SiC and < 1% in the case of GaN) favor the direct epitaxial growth of MoS 2 layers on these substrates. The nucleation and growth of highly oriented and nearly unstrained triangular MoS 2 domains are obtained on the GaN(0001) basal plane by chemical vapor deposition (CVD) at temperatures of 700-800 °C.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of basal planes or edge sites is important for anticipated applications of this material. Horizontally aligned films are suitable for electronics , and optoelectronics, such as ultrafast tunnel diodes or photodetectors for use in harsh environments. Vertically aligned MoS 2 is a promising candidate for substituting noble-metal catalysts in electrochemical hydrogen production conversion of CO 2 to energy-rich products, water disinfection, water splitting, or solar cells .…”
Section: Introductionmentioning
confidence: 99%
“…While vertically standing MoS 2 exposing edges can be interesting for catalysis and hydrogen evolution reaction (HER) applications, [27] layered MoS 2 films uniformly covering the SiC(0001) basal plane are highly attractive as building blocks of heterojunction devices exploiting vertical current transport at MoS 2 /SiC interfaces. These can find application both in the state-of-theart 4H-SiC technology (Schottky and Junction Barrier Schottky diodes) for energy-efficient power conversion, [28] as well as for the implementation of novel device concepts for ultra-fast switching, including p + -MoS 2 /n + -SiC Esaki diodes [29] and vertical hot electron transistors with a n-MoS 2 base [30,31] and n + -SiC emitter. Besides the reported studies, a more comprehensive understanding of the structural properties and of the mechanisms ruling current transport across MoS 2 /SiC interfaces is mandatory for the future development of these heterojunction devices.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the reported studies, a more comprehensive understanding of the structural properties and of the mechanisms ruling current transport across MoS 2 /SiC interfaces is mandatory for the future development of these heterojunction devices. However, to date, only a few studies reported on the electronic transport in MoS 2 /SiC diodes, mainly focused on anisotype (p/n) junctions of p + MoS 2 with n + 4H-SiC, [12,29] whereas there is a lack of knowledge on the isotype (n/n) MoS 2 /4H-SiC heterojunctions.…”
Section: Introductionmentioning
confidence: 99%